PSYCHOLOGICAL, SOCIAL, AND EXISTENTIAL ASPECTS OF THE PHENOMENON OF LONELINESS - Sobirjonova, Mukhlisa (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article reviews studies aimed at elucidating the phenomenological model of the phenomenon of loneliness. Within the framework of phenomenology, various forms of loneliness associated with internal and external factors are studied. Based on the classification of loneliness developed by G. Kolbel and D. Gaev’s views on loneliness, the specific features of this phenomenon are analyzed. The interactionist model of R. S. Weiss provides an opportunity to identify types of loneliness that arise as a result of a lack of social and emotional connections. This article reveals the universal and various levels of manifestation of loneliness, as well as its inextricable connection with social and interpersonal factors